The effect of uterine artery embolization on fertility preservation in the treatment of symptomatic uterine fibroids - Magdalena Zapała; Agnieszka Środoń; Monika Łapaj; Joanna Wilk; Małgorzata Maria Cholewa; Małgorzata Chyćko; Agata Kromer; Katarzyna Cichoń; Agnieszka Gawryś; Julia Czarnota (Journal of Education, Health and Sport, 2023)
Introduction: Uterine fibroids are the most common benign tumors of the uterus. Most often they are asymptomatic, but in their course there may be ailments such as: abnormal bleeding, anaemia, pain, constipation, problems with urination. These tumors are also one of the many causes of infertility. They are most often detected during a standard ultrasound examination. Pharmacological, minimally invasive and surgical treatment is currently available.